2019
DOI: 10.3892/ijo.2019.4734
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA CASC9 positively regulates CHK1 to promote breast cancer cell proliferation and survival through sponging the miR‑195/497 cluster

Abstract: Accumulating evidence has demonstrated that long non-coding RNAs (lncRNAs) play important roles in the pathogenesis and development of diverse types of human disorders. Cancer susceptibility candidate 9 (CASC9), a gene encoding a lncRNA, has frequently been reported to be dysregulated and has been implicated in multiple types of human malignancies. However, the biological role of lncRNA CASC9 in breast cancer (BC) remains largely unknown. The present study aimed to investigate the role of lncRNA CASC9 in BC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 51 publications
(47 reference statements)
1
24
0
Order By: Relevance
“…LncRNA CASC9 facilitates glioma tumorigenesis by sponging miR-519d 30 . LncRNA CASC9 plays an oncogenic role in breast cancer by sponging the miR-195/497 cluster 31 . In this study, we first used bioinformatics tools to predict that CASC9 is predominantly localized to the cytoplasm of CRC cells, which was subsequently verified by a subcellular fractionation assay in CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA CASC9 facilitates glioma tumorigenesis by sponging miR-519d 30 . LncRNA CASC9 plays an oncogenic role in breast cancer by sponging the miR-195/497 cluster 31 . In this study, we first used bioinformatics tools to predict that CASC9 is predominantly localized to the cytoplasm of CRC cells, which was subsequently verified by a subcellular fractionation assay in CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Shao et al proved that lncRNA CASC9 may be used as a novel therapeutic target and as a potential diagnostic marker for BC. 33 Huang et al identified a panel of serum noncoding RNAs (ncRNAs) as potential diagnostic and prognostic biomarkers for BC that included the ncRNAs let-7a, miR-155, miR-574-5p, and MALAT1. 34 Based on our experiments, we found that exosomal H19 could effectively distinguish BC patients from BBD and NC subjects with a significantly high AUC value of 0.870 as well as a sensitivity of 87.0% and a specificity of 70.6%.…”
Section: Discussionmentioning
confidence: 99%
“…4 lncRNAs act as signaling molecules, scaffolds, and instructors, and exert their influence at several levels including transcription, post-transcription, and translation. 5 In recent years, abundant evidence has revealed that anomalous expression of lncRNAs such as HOXD-AS1, H19, CASC9, and NORAD [6][7][8][9] may drive the pathogenesis of breast cancer. In addition, anomalous expression of lncRNAs may serve as a biomarker for breast cancer.…”
Section: Introductionmentioning
confidence: 99%